The Implication of Local Wisdom-Based Geographical Curriculum and its Course Book on the Cosmocentric Attitude of the Students in Bali Upland Region - Ida Bagus Made Astawa (Universitas Pendidikan Ganesha, 2022)
The ability of teachers in Bali to write lesson plans that contain local wisdom is also low, while the competence of local wisdom is high. It happens because the teacher does not yet have a guideline to be used as a reference in compiling the syllabus and lesson plans. This study aims to analyze the implications of applying the geography curriculum based on local wisdom and its textbooks to the cosmocentric attitude of high school students in the highlands of Bali. This study was designed as a